THE EFFECT OF LIQUIDITY, LEVERAGE, PROFITABILITY ON TAX AGGRESSIVENESS WITH FIRM SIZE AS MODERATION - Supriyatno, Agus; Kismanah, Imas; Kimsen, Kimsen; Pagandi, Ahmad (Univesitas Muhammadiyah Tangerang, 2025)
This study is to determine the effect of Liquidity, Leverage, Profitability, on Tax Aggressiveness and Firm Size as moderating variables. This research uses a quantitative approach, the research sample is 19 companies. The sampling technique used was purposive sampling, namely a sample research technique with certain considerations using Eviews 12 software. The research method used in this analysis was the Chow test, Hausman test, Lagrange Multiplier test with the selected model, namely the Random effect model. The results of the simultaneous hypothesis research show that the Leverage and Profitability variables have a significant effect on Tax Aggressiveness (ETR). The results of the partial hypothesis research Leverage and Profitability have no effect on Tax Aggressiveness. While Profitability has an effect on Tax Aggressiveness. Company Size does not moderate Liquidity and Leverage on Tax Aggressiveness while Company Size can moderate the effect of Profitability on Tax Aggressiveness